Prioritization of Research on Drought Assessment in a Changing Climate - Joel Lisonbee; Britt Parker; Erica Fleishman; Trent W. Ford; R. Kyle Bocinsky; Gretel Follingstad; Abby G. Frazier; Zachary H. Hoylman; Amy R. Hudson; John W. Nielsen‐Gammon; Natalie A. Umphlett; Elliot Wickham; et al. (Earth's Future)
Abstract Drought is a period of abnormally dry weather that leads to hydrological imbalance. Drought assessments determine the characteristics, severity, and impacts of a drought. Climate change adds conceptual and quantitative challenges to traditional drought assessments. This paper highlights the challenges of assessing drought in a climate made non‐stationary by human activities or natural variability. To address these challenges, we then identify 10 key research priorities for advancing drought science and improving assessments in a changing climate. The priorities focus on improving drought indicators to account for non‐stationarity, evaluating drought impacts and their trends, addressing regional differences in non‐stationarity, determining the physical drivers of drought and how they are changing, capturing precipitation variability, and understanding the drivers of aridification. Ultimately, improved drought assessments will inform better risk management, adaptation strategies, and planning, especially in areas where climate change significantly alters drought dynamics. This perspective offers a path toward more accurate and effective drought management in a non‐stationary climate system.